Fourth Symposium on Fatigue and Fracture of Metallic Medical Materials and Devices - Mitchell, M. R. 1941-; Berg, Brian, 1958-; Woods, Terry, 1960-; Jerina, Kenneth L. (Selected technical papers, 2019)
"Contains peer-reviewed papers that were presented at a symposium held May 2223, 2018, in San Diego, California, USA. The symposium was jointly sponsored by ASTM International Committee E08 on Fatigue and Fracture, Subcommittee E08.05 on Cyclic Deformation and Fatigue Crack Formation, Committee F04 on Medical and Surgical Materials and Devices, and Subcommittee F04.15 on Material Test Methods."